Development of a biocompatible 3D hydrogel scaffold using continuous liquid interface production for the delivery of cell therapies to treat recurrent glioblastoma - Lauren Kass; Morrent Thang; Yu Zhang; Cathleen DeVane; Julia Logan; Addis Tessema; Jillian Perry; Shawn Hingtgen (Wiley, 2024)
Abstract Glioblastoma (GBM) is the most common primary malignant brain tumor diagnosed in adults, carrying with it an extremely poor prognosis and limited options for effective treatment. Various cell therapies have emerged as promising candidates for GBM treatment but fail in the clinic due to poor tumor trafficking, poor transplantation efficiency, and high systemic toxicity. In this study, we design, characterize, and test a 3D‐printed cell delivery platform that can enhance the survival of therapeutic cells implanted in the GBM resection cavity. Using continuous liquid interface production (CLIP) to generate a biocompatible 3D hydrogel, we demonstrate that we can effectively seed neural stem cells (NSCs) onto the surface of the hydrogel, and that the cells can proliferate to high densities when cultured for 14 days in vitro. We show that NSCs seeded on CLIP scaffolds persist longer than freely injected cells in vivo, proliferating to 20% higher than their original density in 6 days after implantation. Finally, we demonstrate that therapeutic fibroblasts seeded on CLIP more effectively suppress tumor growth and extend survival in a mouse model of LN229 GBM resection compared to the scaffold or therapeutic cells alone. These promising results demonstrate the potential to leverage CLIP to design hydrogels with various features to control the delivery of different types of cell therapies. Future work will include a more thorough evaluation of the immunological response to the material and improvement of the printing resolution for biocompatible aqueous resins.